ENHANCING SPEAKING SKILL THROUGH AI-POWERED TECHNOLOGY - Liya Umaroh; Mukaromah Mukaromah; Muhammad Naufal (Seminar Nasional Teknologi dan Multidisiplin Ilmu (SEMNASTEKMU), 2023)
. Artificial Intelligent (AI) is a field of computer science devoted to solve cognitive problems, commonly associated with human intelligence, such as learning, problem solving and pattern recognition. From education point of views, it helps teachers to facilitate learning process especially for speaking skill. The research method runs with mixed method (qualitative. And quantitative) The aim of this research is investigating the students’ speaking performance with artificial intelligence. The data collection is taken from interviews, photo, and literature studies. The result of this study is the increasing student’s speaking performance with AI.